Resistant Hypertension Secondary to Large Vessel Vasculitis in Adult Female - Satwick, V.; Anuradha, N.; Preethi, Anis (Journal of Neonatal Surgery, 2025)
Takayasu arteritis (TA) is an uncommon chronic inflammatory condition targeting large arteries, especially the aorta and its major branches, and often results in vessel narrowing or occlusion . It is characterized by granulomatous inflammation of the vascular layers leading to thickening, causing stenosis and occlusion along with microaneurysms. TA is more common in young females with a female-to-male ratio of 8:1. This case involved a 37-year-old female who presented with headache, giddiness, and left upper limb pain. She had elevated blood pressure with unequal limb measurements, raising suspicion of TA. Treatment with high-dose prednisolone and methotrexate improved the patient's symptoms and reduced the levels of inflammatory markers. This case report is to emphasize the importance of considering TA as one among the causes of secondary hypertension, particularly in young women, and highlight the value of early diagnosis and appropriate management in preventing end organ damage